A Study of the Pink Tax Mess in the Current Consumer Era - Li, Yingyue (Transactions on Social Science, Education and Humanities Research, 2024)
With the progress of society and the promotion of women’s status, women are playing an increasingly important role in the consumer market. As a kind of gender discrimination phenomenon, pink tax is widespread in the consumer market. It not only damages the interests of female consumers and the level playing field of the market, but also hinders the healthy development of women’s consumer market. This paper aims to explore the causes, influences and solution strategies of pink tax chaos through the combination of direct and indirect laws, to provide a useful reference for protecting consumer rights and fair market competition. The government, consumers, enterprises and all sectors of society should make joint efforts to strengthen the construction of laws and regulations, improve the awareness of the protection of consumer rights and interests, advocate corporate social responsibility and moral management, strengthen the supervision of public opinion, and jointly promote the solution of the pink tax problem and the healthy development of the female consumer market.